Cumulative contextual risk, maternal responsivity, and social cognition at 18 months. (14th July 2014) - Belsky, Jay; van IJzendoorn, Marinus H.; Wade, Mark; Moore, Chris; Astington, Janet Wilde; Frampton, Kristen; Jenkins, Jennifer M.
Abstract By 18 months children demonstrate a range of social–cognitive skills that can be considered important precursors to more advanced forms of social understanding such as theory of mind. Although individual differences in social cognition have been linked to neurocognitive maturation, sociocultural models of development suggest that environmental influences operate in the development of children's social–cognitive outcomes. In the current study of 501 children and their mothers, we tested and found support for a model in which distal environmental risk, assessed when children were newborns, was indirectly associated with children's social–cognitive competency at 18 months through mothers' responsivity at 18 months. Part of this effect also operated through children's concomitant language skills, suggesting both a language-mediated and a language-independent mechanism of social–cognitive development. These findings are discussed with respect to the Vygotskian themes of internalization and semiotic mediation.